Year of the Mer - Lewis, L. D. (Saga Press, 2026)
Yemi's grandmother Arielle might have gotten her happily-ever-after, but her granddaughter Yemi is having a much harder time. Her father, the king of Ixia, was assassinated years ago, her mother is slowly dying of a poisoned wound, and she faces whispers and slights from her own people. Yemi has been raised as the shield of the kingdom and is soon to inherit the throne, but she cannot shake her fury at how Ixia has treated her family after all they've sacrificed. Only her patient mother and steadfast personal bodyguard (and fiancée), Nova, help Yemi rein in that fury...most of the time. When the kingdom's discontented rumblings reach a fever pitch, a coup erupts and Yemi's throne is usurped, stripping her of her family and forcing her into exile. Now, only one being has the power to help her: Ursla. Like her grandmother before her, Yemi is tempted by a deal with the sea-witch. With powerful and ancient magic behind her, Yemi could avenge her family, take back her throne, and protect the love of her life. But she should know more than anyone that there is always a price. As much as Yemi wants vengeance, Ursla has been waiting a very, very long time for her own-and it may take more fortune than Yemi possesses to keep her from losing everything all over again.